"We learnt it, then we lived it": Influencing medical students' intentions toward rural practice and generalist careers via a socially-accountable curriculum. (2nd January 2021) - Woolley, Torres; Ross, Simone; Larkins, Sarah; Sen Gupta, Tarun; Whaleboat, Donald
Abstract: Objective: The James Cook University (JCU) medical school has a mission to produce graduates committed to practising with underserved populations. This study explores the views of final-year students regarding the influence of the JCU medical curriculum on their self-reported commitment to socially-accountable practice, intentions for rural practice, and desired postgraduate training pathway. Methods: Cross-sectional survey of final year JCU medical students ( n  = 113; response rate = 65%) to determine whether their future career directions (intentions for future practice rurality and postgraduate specialty training pathway) are driven more by altruism (commitment to socially accountable practice/community service) or by financial reward and/or prestige. Results: Overall, 96% of responding students reported their JCU medical course experiences had cultivated a greater commitment towards 'socially-accountable' practice. A commitment to socially-accountable practice over financial reward and/or prestige was also significantly associated with preferring to practise Medicine in non-metropolitan areas ( p  = 0.036) and intending to choose a 'generalist' medical discipline ( p  = 0.003). Conclusions: The findings suggest the JCU medical curriculum has positively influenced the commitment of its graduating students towards more socially accountable practice. This influence is a likely result of pre-clinical teachings around health inequalities and socially-accountable medical practice in combination with real-world, immersive experiences on rural and international placements.